2018
DOI: 10.1016/j.atmosenv.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Time effects of high particulate events on the critical conversion point of ground-level ozone

Abstract: A B S T R A C TParticulate matter (PM), especially those with an aerodynamic particle size of less than 10 μm (PM 10 ), is typically emitted from transboundary forest fires. A large-scale forest fire may contribute to a haze condition known as a high particulate event (HPE), which has affected Southeast Asia, particularly Peninsular Malaysia, for a long time. Such event can alter the photochemical reactions of secondary pollutants. This work investigates the influence of PM on ground-level ozone (O 3 ) formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…During nighttime, O3 concentrations for CMCO and RMCO is consistently showed values that were less than 10 ppb indicating very minimal O3 concentrations present in the air during the periods. Similar trends have also been reported by Awang et al [14] when investigating the influence of particulate matter (PM) on O3 formation during high particulate events. The study reported that the are shift in O3 critical conversion time due to the screening effect of a PM that promotes attenuation of sunlight.…”
Section: Diurnal Variationssupporting
confidence: 87%
See 1 more Smart Citation
“…During nighttime, O3 concentrations for CMCO and RMCO is consistently showed values that were less than 10 ppb indicating very minimal O3 concentrations present in the air during the periods. Similar trends have also been reported by Awang et al [14] when investigating the influence of particulate matter (PM) on O3 formation during high particulate events. The study reported that the are shift in O3 critical conversion time due to the screening effect of a PM that promotes attenuation of sunlight.…”
Section: Diurnal Variationssupporting
confidence: 87%
“…The study reported that the are shift in O3 critical conversion time due to the screening effect of a PM that promotes attenuation of sunlight. Similar shifting might also contribute to changes in precursors concentrations [14].…”
Section: Diurnal Variationsmentioning
confidence: 99%
“…Overall, variations in O 3 at night have been studied, and the possible factors that contribute to the presence of O 3 at night have been analysed [14][15][16][17][18]. Nighttime O 3 variations are attributed to the weakening of vertical mixing at night [18] and the effects of emissions and meteorological factors [14][15][16]19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution can be defined as the presence in the atmosphere of one or more contaminants in such quantities and for such duration as is injurious or tends to be injurious, to human health, human welfare, animal or plant life and the environment (Latif et al, 2012;Singal, 2012;Awang et al, 2018). Atmospheric pollution is caused by both natural and anthropogenic sources.…”
Section: Introductionmentioning
confidence: 99%